Multistage Encryption for Text Using Steganography and Cryptography - Mohammed Majid Msallam; Fayez Aldoghan (Journal of Techniques)
Recently, the movement of data between smart devices has piqued the world's curiosity because it transmits important and unimportant data via the Internet. Thus, important data must be encrypted during passing over a network so that information can only access by an intended receiver and processed by it. As a result, information security has become even more critical than before. Our proposal suggests a method to secure data in three stages using cryptography and steganography. The important message will divide into two parts a part will encrypt by Caesar Cipher and another by Vigenere Cipher. The ciphertext will process by Morse code and will then hide in a cover image using Least Significant Bits (LSB) technique. According to the value the of peak signal-to-noise ratio (PSNR) obtained in this work our proposal has an extra security level and robustness. Finally, our research provides more security because of the mixture between cryptography and steganography.